“A small and great city”: On Translating Contemporary Glasgow - Lewandowska-Rodak, Dominika (Text Matters: A Journal of Literature, Theory and Culture, 2025)
The aim of this article is to explore contemporary literary depictions of Glasgow as material for translation into Polish. Urban literature constitutes both a challenge and an opportunity for translators, due to the paradoxical nature of the modern Western city—on the one hand, culture-specific, and on the other, generic, resembling all the other Western cities. As such, urban space epitomises the ambiguous nature of contemporary Western cultures themselves, a fact that is made especially evident in translation, a process/product of cultural interaction through which matters of locality and globality unavoidably come to the fore. This analogy between urban space and culture, while universal, seems particularly relevant to discussions of non-canonical cities, with Glasgow being a prominent example. Since the 1980s and 90s, Scotland’s largest city has been a crucial spot on the country’s literary map, a territory where globalised urbanism converges with a continued quest for a distinct national, cultural, and linguistic selfhood. Drawing on works by such authors as Alasdair Gray, James Kelman, Denise Mina, and Douglas Stuart, this article explores the image(s) of Glasgow conceived in Scottish fiction of the late 20th and 21st centuries, and examines the city’s renditions in Polish. By doing so, I hope to illuminate the complexities of the contemporary Scottish national self as reflected in Glasgow writing, to investigate how they have been—and can be—approached in translation, and, in the process, to shed some light on the Polish translational handling of cultural and linguistic markedness.